Influence of additional stress caused by mining subsidence on blast furnace in metallurgical mining area - W. L. Fu; L. W. You (Metalurgija, 2024)
Underground goaf in metallurgical mining area leads to surface subsidence and has destructive effect on blast furnace. This paper studies the influence of underground goaf on blast furnace.The overlying strata and surface subsidence due to the formed gob area after the underground mining led to a different degree of destruction to blast furnace. Hence, blast furnace was modeled to theoretically analyze the additional stress applied to blast furnace body and foundation when withstanding the surface deformation. On this basis, the anti-deformation structure was designed to analyze the influences of Class I - IN surface deformation on the setting of Blast furnace body unit.